ANALISIS EFEKTIVITAS STRATEGI PROMOSI DIGITAL PADA USAHA KECIL MENENGAH (UKM) BERBASIS ONLINE DI KABUPATEN BONE - Karmila, Karmila; Haris, Abdul (Universitas Ichsan Sidenreng Rappang, 2025)
Digital transformation has brought significant changes to the marketing strategies of small and medium enterprises (SMEs), including those in Bone Regency. This study aims to analyze the digital promotion strategies implemented by online-based SME actors and to evaluate the effectiveness and challenges in their implementation. The research uses a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. The results of the study show that most SME actors have utilized social media and marketplaces such as Instagram, Facebook, WhatsApp Business, and TikTok Shop. However, the use of more advanced digital marketing features such as paid advertising and analytics remains very limited. The main challenges include low digital literacy and limited access to training. Nevertheless, there are significant opportunities through the growing trend of online shopping and the potential for collaboration with local influencers. Two business actors who applied educational content strategies and two-way communication successfully increased their sales significantly. This study recommends the need for more structured digital marketing training for SME actors to improve promotional effectiveness and business competitiveness in a sustainable manner.